2012
DOI: 10.1007/s00414-012-0734-2
|View full text |Cite
|
Sign up to set email alerts
|

Drying properties of bloodstains on common indoor surfaces

Abstract: When blood reaches an extracorporeal surface, a drying process is initiated. Properties of this drying process may be crucial for the correct assessment of case-specific time lapses, however, there is a lack of systematic studies concerning the drying times of blood. We present a study on drying properties of small blood droplets with a standardized size of 25 μl (resembling droplets originating from pointed and sharp objects, e.g. the tip of a knife) under different environmental conditions to elucidate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…Blood dries relatively quickly depending on the temperature, humidity and presence/absence of wind [79][80][81]. A study by van Oorschot et al [82] showed that blood (15 and 30 µl) on a hard non-porous substrate will dry within 30-60 min (quicker in warmer temperatures), and that the transfer rates of blood, 5 min after deposition, declines exponentially until the deposit is dry.…”
Section: Source and Freshness /Moisture Contentmentioning
confidence: 99%
“…Blood dries relatively quickly depending on the temperature, humidity and presence/absence of wind [79][80][81]. A study by van Oorschot et al [82] showed that blood (15 and 30 µl) on a hard non-porous substrate will dry within 30-60 min (quicker in warmer temperatures), and that the transfer rates of blood, 5 min after deposition, declines exponentially until the deposit is dry.…”
Section: Source and Freshness /Moisture Contentmentioning
confidence: 99%
“…A análise do padrão das manchas de sangue como a distribuição, forma, contorno e tamanho pode substancialmente contribuir na reconstrução de eventos em cenas do crime [11]. O luminol se mostrou eficiente mesmo quando a quantidade de sangue é diminuta [12] como no caso da parede analisada.…”
Section: Discussionunclassified
“…Bloodstain pattern appearance, however, may differ greatly depending on which fabric or underground they are on. Several studies have been performed dealing with influences of drop volume, dropping height and impact angle [4,22], drying properties [16], heated surfaces [9], different fabrics [4], as well as dark fabrics [5][6][7]18]. Bloodstains on dark surfaces bring along a considerable difficulty because of low contrast to the surface bloodstains are difficult or even impossible to detect with the unaided human eye.…”
Section: Introductionmentioning
confidence: 99%